HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN PENYESUAIAN DIRI ORANG TUA YANG MEMILIKI ANAK AUTIS - Aziz, Abdul (Universitas Sahid Surakarta, 2013)
A disruption in childhood who became frightened most mothers today is autism. According Hopes and Harris (in Berkell, 1992), a mother with an autistic child will experience greater stress than mothers with children who have mental retardation due to loss of critical interpersonal responses in the autistic children. The purpose of the study The purpose of this study was to determine the relationship between social support to adjustment in mothers of children with autism. And to find out how big the role of social support on adjustment to parents (mothers) of children with autism. The research subject of autistic children who were fostered (in therapy / consultation) in the institution